2018
DOI: 10.4236/jep.2018.93018
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilization by <i>Bacillus subtilis</i> and <i>Serratia marcescens</i> Isolated from Tomato Plant Rhizosphere

Abstract: Plants need phosphorus for many physiological activities in a form of phosphate anions. Three different bacterial strains (Bacillus subtilis PH, Serratia marcescens PH1, and Serratia marcescens PH2), recently isolated from tomato plant rhizosphere, have high phosphate solubilization index (SI from 2.8 to 3.2) on Pikovskaya agar medium (which contains calcium phosphate). Moreover, phosphate release from calcium in Pikovskaya broth over 5 days is increasing with cell growth for the different isolates. The most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 40 publications
3
18
1
4
Order By: Relevance
“…showed the highest phosphate-solubilizing capability with a PSI value of 3.05 ± 0.13 after 6 days incubation, higher than the report from Sengupta et al [24] and Yasmin and Bano [25] that tested on Picovskaya's agar media using tricalcium phosphate as the sole P source. Previous studies reported that the most significant solubilizers of phosphate are mainly belonging to Bacillus and Pseudomonas [12,[26][27][28]. However, in our study, Burkholderia species were easier to be isolated and showed a high phosphate-solubilizing potential (Figure 4).…”
Section: Discussioncontrasting
confidence: 48%
“…showed the highest phosphate-solubilizing capability with a PSI value of 3.05 ± 0.13 after 6 days incubation, higher than the report from Sengupta et al [24] and Yasmin and Bano [25] that tested on Picovskaya's agar media using tricalcium phosphate as the sole P source. Previous studies reported that the most significant solubilizers of phosphate are mainly belonging to Bacillus and Pseudomonas [12,[26][27][28]. However, in our study, Burkholderia species were easier to be isolated and showed a high phosphate-solubilizing potential (Figure 4).…”
Section: Discussioncontrasting
confidence: 48%
“…As, PGPB enhance phytoremediation by the production of siderophores (Tahir et al, 2013), phytohormones, and chelators in addition to their ability to biodegrade contaminants and facilitate their removal (Chun et al, 2020) or S. marcescens ABHI001 in the bioremediation of organic pollutants, such as p-cresol (Singh et al, 2017). Also, PGPB used as a biofertilizer can dissolve phosphate highly and making available for plants (Akhtar et al, 2012;Mohamed et al, 2018). Besides, PGPB can be mixed with different agrochemicals e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, PGPB can be mixed with different agrochemicals e.g. mineral fertilizers and pesticides without reducing its efficiency (Esfahani et al, 2016;Mohamed et al, 2018;Saedi et al, 2017). PGPB showed potency against a wide range of pests e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial clones with clear halo zone in phosphate media were considered as PSB and selected for further use. The phosphate solubilizing index (PSI) was calculated as the following equation [20,21]. PSI = (colony diameter + halozone diameter)/colony diameter ×100.…”
Section: Isolation Of Microbe With P-solubilizing Activitymentioning
confidence: 99%